2021
DOI: 10.3390/app11209631
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Adsorption Capacity for CO2 in Reduced Graphene Oxide (rGO) and Modified Ones with Different Heteroatoms in Relation to Surface and Textural Characteristics

Abstract: Reduced graphene oxide is a material that has a variety of applications, especially in CO2 adsorption. The study of this research is the preparation of reduced graphene oxide with different heteroatoms and how the adsorption capacity is changed. The functionalization with other compounds bearing Si, S, N, and O was before reducing graphene oxide. Different monoliths were prepared by changing the ascorbic acid analogy and the temperature of reduction. The different porosity values, percentages of heteroatoms, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…This excellent adsorption performance is attributed to increased surface area at higher reduction temperatures, owing to the significant removal of oxygen functional groups and increased pore volume. After removing surcial oxygen functionalities, graphene's sp 2 - hybridized structure was partially restored at 250 °C 41 , 42 .…”
Section: Resultsmentioning
confidence: 99%
“…This excellent adsorption performance is attributed to increased surface area at higher reduction temperatures, owing to the significant removal of oxygen functional groups and increased pore volume. After removing surcial oxygen functionalities, graphene's sp 2 - hybridized structure was partially restored at 250 °C 41 , 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Graphene oxide, including reduced graphene oxide and its various modifications, is a group of materials with a wide range of applications, especially for CO 2 adsorption. In order to improve the properties of this material, the possibilities of its functionalization with various heteroatoms (Si, S, N, O) containing compounds have been studied, as a result of which materials with increased porosity and surface area are obtained [108]. The surface areas (BET) of reduced graphene oxides and modified graphene oxides studied by Politakos [108] are in the range of 70-351 m 2 /g, and their CO 2 adsorption capacities are in the range of 0.47-1.67 mmol/g (25 • C, atmospheric pressure).…”
Section: Carbon Dioxide Adsorption Onto Mof-composite Adsorbentsmentioning
confidence: 99%
“…In order to improve the properties of this material, the possibilities of its functionalization with various heteroatoms (Si, S, N, O) containing compounds have been studied, as a result of which materials with increased porosity and surface area are obtained [108]. The surface areas (BET) of reduced graphene oxides and modified graphene oxides studied by Politakos [108] are in the range of 70-351 m 2 /g, and their CO 2 adsorption capacities are in the range of 0.47-1.67 mmol/g (25 • C, atmospheric pressure). Thus, it can be concluded that raw biochar is an equivalent CO 2 adsorbent, as it shows similar CO 2 adsorption capacities, which can be increased by forming composites with, for example, CuBTC or UiO-66-BTEC.…”
Section: Carbon Dioxide Adsorption Onto Mof-composite Adsorbentsmentioning
confidence: 99%
“…Graphene oxide has been reported as an efficient adsorbate for acid gases due to the high surface area it provides and stable chemical structure . Some researchers have investigated the physisorption of CO 2 on graphene oxide (GO), reduced graphene oxide (rGO), and amine-functionalized graphene oxide. , One advantage of the GO structure is that it consists of oxygen-rich groups such as hydroxide and epoxide groups attached to the surface and carboxyl and carbonyl groups on the edges. These oxygen-rich functional groups are the common reaction sites for a wide range of chemical reactions …”
Section: Introductionmentioning
confidence: 99%